A pediatric case and literature review of mucormycosis: Diagnostic and treatment challenges in a resource poor setting - Lubis, Inke ND.; Farah, Sara; Pasaribu, Ayodhia P.; Evalina, Rita; Daulay, Rini S.; Wijaya, Hendri (Narra Sains Indonesia, 2023)
Mucormycosis is an emerging disease that primarily affects immunocompromised patients; however, it has also been reported in immunocompetent individuals. Studies in the pediatric population are limited and reported mostly in case studies or series. The aim of this case report is to present a pediatric mucormycosis originated from Sumatra Island, Indonesia. A 13-year-old boy was referred to a tertiary hospital with facial necrosis involving the nasal, oral, and left maxillary areas, as well as left periorbital edema. No known underlying conditions were documented. The diagnosis was confirmed by histopathological findings of broad, pauci-septate, ribbon-like hyphae branching at 90°. The patient was managed by a multidisciplinary team consisting of the ear, nose, and throat, infectious diseases, dermatology, surgery, microbiology, and pathology departments. Management of the patient included debridement of the necrotic lesion and antibiotics and anti-fungal (fluconazole). Due to unavailability, the patient was not treated with amphotericin B. The patient died after 30 days of admission. This case highlights the importance of maintaining a high suspicion of invasive mucormycosis, even in immunocompetent children, when symptoms and signs are present, especially in resource-limited settings.